The Existential Elucidation of Evil (Existential Analysis: Journal of the Society for Existential Analysis, 2006)
The present paper is a revised version of a talk given at the Third Central- and Eastern European Conference on Phenomenology that had as its focus the theme Subjectivity, Intentionality, Evil (In memory of Józef Tischner, 1931-2000), and held in Warsaw, Poland, November 26-28, 2004. Its purpose is, first, to present an existential elucidation of the mystery of evil, as found in the works of Marcel and Jaspers; and second, to explore the consequences of their analyses for a potential phenomenology of evil. Expanding on their existential analyses of evil, the author of this paper will argue that evil arises in the clash between two fundamental forms of freedom. There is the freedom of choice, in which we have the power to know and to act with a purpose; and there is a deeper primordial freedom – the opportunity for unconditional action in boundary situations. Specifically, evil arises from a failure to risk oneself in unconditional communication with another, at the ultimate limits of what is possible. The mystery of evil then, is more profound than a misdirection of the will and cannot be illuminated by means of a phenomenology limited to an intentional analysis of 'evil acts', but can only be grasped in its existential dimensions.